Oxford American children's encyclopedia. Volume 7, stomachs-zoos. (New York : Oxford University Press, 1998)
Presents alphabetically arranged articles covering a wide range of human knowledge.
3-6
Keywords: Children's encyclopedias and dictionaries; Encyclopedias and dictionaries; Encyclopedias and dictionaries